Implementasi DC-DC Boost Converter Menggunakan Arduino Berbasis Simulink Matlab - Muldi Yuhendri; Randy Setiawan (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Direct current (dc) voltage sources are one of the voltage sources most widely used for various purposes. Dc voltage can be obtained from a dc generator or by converting an ac voltage into a dc voltage using a power converter. There are several dc voltage levels that are commonly used by electrical and electronic equipment. To get a dc voltage that can be used for various equipment, then a dc voltage source must be varied according to the required. One way to get a variable dc voltage is to use a dc-dc converter. This research proposes a dc-dc boost converter that can increase the dc voltage with varying outputs. The boost converter is proposed using Arduino Uno as a controller with an input voltage of 12 volts. The converter output voltage regulation is implemented through Arduino programming using Matlab simulink. The experimental results show that the boost converter designed in this study has worked well as intended. This can be seen from the boost converter output voltage which is in accordance with the reference voltage entered in the Matlab simulink program